Antecedents and Consequences of Group Potency: A Study of Self-Managing Service Teams - de Jong, Ad; de Ruyter, Ko; Wetzels, Martin (Management Science, 2005)
This paper proposes and tests a model of antecedents and consequences of group potency in self-managing teams in retail banking. Based on data collected from boundary-spanning service employees organized in 60 teams and their customers, our findings reveal a significant positive impact of group potency on customer-perceived service quality and a negative effect on service profitability. In addition, we find that team consensus regarding group potency positively moderates the effects of group potency, so that for teams with higher levels of potency consensus, the positive impact of group potency on customer-perceived service quality is stronger, whereas the negative impact of group potency on service productivity is weaker. Furthermore, we find significant positive effects of management and interteam support and functional diversity as well as a significant negative effect of team tenure on individual team member beliefs of group potency. Finally, social support consensus moderates the effects of management support, interteam support, and team tenure on group potency, so that the effects of these antecedents are weaker for teams with higher levels of social support consensus. Thus, we conclude that team confidence consensus increases the positive impact of group potency on customer perceptions of service quality and decreases the negative impact on profitability. Thus, team-member perceptual agreement on their team's potency should be stimulated.